Fecal Klebsiella pneumoniae Carriage Is Intermittent and of High Clonal Diversity - Lepuschitz, Sarah; Hauser, Kathrin; Schriebl, Agnes; Schlagenhaufen, Claudia; Stöger, Anna; Chakeri, Ali; Vötsch, Kornelia; Pekard-Amenitsch, Shiva; Springer, Burkhard; Allerberger, Franz; Ruppitsch, Werner (Frontiers in Microbiology, 2020)
The Klebsiella pneumoniae complex comprises several closely related entities, which are ubiquitous in the natural environment, including in plants, animals, and humans. K. pneumoniae is the major species within this complex. K. pneumoniae strains are opportunistic pathogens and a common cause of healthcare-associated infections. K. pneumoniae can colonize the human gastrointestinal tract, which may become a reservoir for infection. The aim of this study was to investigate the fecal K. pneumoniae carriage in six healthy individuals during a 1 year period. Stool samples were obtained once a week. Using direct and pre-enriched cultures streaked on ampicillin-supplemented agar plates, up to eight individual colonies per positive sample were selected for further characterization. Whole genome sequencing (WGS) was performed for strain characterization. Sequence type (ST), core genome complex type (CT), K and O serotypes, virulence traits, antibiotic resistance profiles, and plasmids were extracted from WGS data. In total, 80 K. pneumoniae isolates were obtained from 48 positive cultures of 278 stool samples from five of the six test subjects. The samples of the five colonized volunteers yielded at most two, three, four (two persons), and five different strains, respectively. These 80 K. pneumoniae isolates belonged to 60 STs, including nine new STs; they were of 70 CTs, yielded 48 K serotypes, 11 O serotypes, and 39 wzc and 51 wzi alleles. Four of the five subjects harbored serotypes K20 and K47, as well as STs ST37, ST101, ST1265, and ST20, which had previously been linked to high-risk K. pneumoniae clones. In total, 25 genes conferring antibiotic resistance and 42 virulence genes were detected among all 80 isolates. Plasmids of 15 different types were found among 65 of the isolates. Fecal carriage of individual strains was of short duration: 70 strains were found on a single sampling day only, and 5 strains were isolated in samples collected over two consecutive weeks. Two of the five colonized individuals—working colleagues having meals together—shared identical K. pneumoniae types four times during the study period. Our findings point toward the potential role of food as a reservoir for K. pneumoniae in humans.